ADDRESSING JAWBONE DEFECTS POST-COVID-19 COMPLICATIONS: A MULTIDISCIPLINARY APPROACH TO COMPLEX TREATMENT (Journal of Universal Science Research, 2024)
This thesis addresses the intricate challenges of treating jawbone defects that arise as post-complication phenomena in patients who have recovered from COVID-19. It aims to propose a comprehensive treatment protocol that encompasses both the novel insights into the relationship between severe viral infections and maxillofacial bone health, and the advanced therapeutic approaches available to reconstruct and rehabilitate affected jawbone structures.